Radioimmune Imaging of α4β7 Integrin and TNFα for Diagnostic and Therapeutic Applications in Inflammatory Bowel Disease - Alberto Signore; Rita Bonfiglio; Michela Varani; Filippo Galli; Giuseppe Campagna; Manuel Desco; Lorena Cussó; Maurizio Mattei; Andreas Wunder; Filippo Borri; Maria T. Lupo; Elena Bonanno (MDPI AG, 2023)
Imaging using radiolabelled monoclonal antibodies can provide, non-invasively, molecular information which allows for the planning of the best treatment and for monitoring the therapeutic response in cancer, as well as in chronic inflammatory diseases. In the present study, our main goal was to evaluate if a pre-therapy scan with radiolabelled anti-α4β7 integrin or radiolabelled anti-TNFα mAb could predict therapeutic outcome with unlabelled anti-α4β7 integrin or anti-TNFα mAb. To this aim, we developed two radiopharmaceuticals to study the expression of therapeutic targets for inflammatory bowel diseases (IBD), to be used for therapy decision making. Both anti-α4β7 integrin and anti-TNFα mAbs were successfully radiolabelled with technetium-99m with high labelling efficiency and stability. Dextran sulfate sodium (DSS)-induced colitis was used as a model for murine IBD and the bowel uptake of radiolabelled mAbs was evaluated ex vivo and in vivo by planar and SPECT/CT images. These studies allowed us to define best imaging strategy and to validate the specificity of mAb binding in vivo to their targets. Bowel uptake in four different regions was compared to immunohistochemistry (IHC) score (partial and global). Then, to evaluate the biomarker expression prior to therapy administration, in initial IBD, another group of DSS-treated mice was injected with radiolabelled mAb on day 2 of DSS administration (to quantify the presence of the target in the bowel) and then injected with a single therapeutic dose of unlabelled anti-α4β7 integrin or anti-TNFα mAb. Good correlation was demonstrated between bowel uptake of radiolabelled mAb and immunohistochemistry (IHC) score, both in vivo and ex vivo. Mice treated with unlabelled α4β7 integrin and anti-TNFα showed an inverse correlation between the bowel uptake of radiolabelled mAb and the histological score after therapy, proving that only mice with high α4β7 integrin or TNFα expression will benefit of therapy with unlabelled mAb.